Appraisal of impact of NYSC’s skills acquisition and entrepreneurial development programme (SAED) on entrepreneurial development of ex-corps members (2022)
The study assessed NYSC's Skills Acquisition and Entrepreneurship Development programme (SAED) on the entrepreneurial development of ex-corp members that served between 2015 and 2020. In this study, three research questions were posed and addressed. This study adopted a survey research design. 250 masters' students that have undergone NYSC were randomly selected at the University of Ibadan. Three validated instruments were used to collect data for the study: NYSC's Skills Acquisition and Entrepreneurship Development Programme Scale (ANYSCSAEDPS) (r = 0.76), Benefits and Challenges of NYSC's Skills Acquisition and Entrepreneurship Development Questionnaire (BNYSCSAEQ) (r = 0.84). Data were analyzed using descriptive statistics of frequency counts, percentages, mean and standard deviation. The findings revealed that majority of the ex-corp members during NYSC's (SAED) Programme were exposed to educational skills, tourism and cosmetology, while few were exposed to horticulture and landscaping 15 (5.6 percent), power and energy 14 (9.6%), and automobile 8 (3.2 percent). The study also revealed that SAED was beneficial and very good for youth empowerment. It can therefore, be concluded that the SAED programme is beneficial to graduates' empowerment and the reduction of unemployment among youths, although its contribution to the development of entrepreneurial skills was not adequate enough due to some challenges facing its implementation. Consequently, the government should devote more attention to the programme by making resources available for its smooth implementation. Corps members should be re-oriented on the benefits of participating in SAED through their commitments when enlisting for entrepreneurship training during service, among other things.